PENGARUH MODEL PEMBELAJARAN FLIPPED CLASSROOM TIPE PEER INSTRUCTION FLIPPED BERBANTUAN VIDEO PEMBELAJARAN TERHADAP KEMAMPUAN PEMECAHAN MASALAH DAN KEMANDIRIAN BELAJAR - Auliza, Elsa; Widyastuti, Eri (Universitas Islam Sumatera Utara, 2024)
This study aims to determine the effect of the peer instruction flipped classroom type learning model assisted by learning videos on problem solving skills and student learning independence. This type of research is Quasi Experimental with nonequivalent control group design. This research was conducted at SMP Negeri 1 Perbaungan. The study population amounted to 275 students and the sample amounted to 60 students. Problem solving ability data were collected using tests and learning independence data were collected using questionnaires. The data were analyzed using independent T test. After testing the data on problem solving ability and learning independence, it was found that the alternative hypothesis was accepted. To determine the influence of the independent variable on the dependent variable, the cohen's test was conducted. Based on the cohen's test, it was found that the peer instruction flipped classroom learning model assisted by learning videos had an effect of 86% on students' problem-solving ability and an effect of 82% on students' learning independence.